Efektivitas Penggunaan Influencer Melalui Media Sosial Instagram Terhadap Kenaikan Profit Ditinjau Dari Teori AISAS - Havizatun, Melvi; Amelia, Kiki Putri (Manajemen Inovasi Bisnis dan Strategi, 2025)
This study aims to determine the digital marketing strategy using influencers on Instagram social media at the Urly Women store seen from the AISAS theory and to determine its effect on increasing profits at the store. This study uses a qualitative descriptive research type. Data collection techniques are through observation and interviews. Interactive Analysis Method is used as a data analysis technique to draw conclusions and suggestions Purposive Sampling is used as a sampling technique based on criteria. The number of informants in the study is 5 people (1 owner, 1 influencer, 3 consumers).The results of the study show that influencers are one of the effective tools when promoting on Instagram social media. However, not all AISAS theories can be achieved by using influencers. From the results of interviews with the owner, the use of influencers cannot significantly increase profits but affects the number of followers or viewers on Instagram, which means that consumers only go to the search stage and do not continue to the action and share stages in the AISAS theory.Keywords: Digital Marketing, Influencer, Instagram, AISAS Theory,URLVWomen